Systems Engineering as a critical tool in mobile robot simulation - Citlalih Gutiérrez Estrada (International Journal of Combinatorial Optimization Problems and Informatics, 2013)
This paper explains a mobile robot simulation process in a static scenario with obstacles, which generated a location map supported by various prototypes created throughout the project, used to analyze the behavior of autonomous navigation algorithms and implemented mapping. This project had the management and formalization support from Software Systems Engineering through the spiral lifecycle model, used to develop and test the intended processes and human reasoning. Each step of the spiral lifecycle model iteration considered the goals, artificial intelligence (AI) and simulation aspects by identifying the robot's purpose, as well as solution alternatives to define the methods to achieve the intended goals. As a project with a common objective for a multidisciplinary research group, the work and results obtained by means of systems engineering allowed tackling the interests of several end users and handling functional and non-functional requirements separately.